Mitochondrial dynamics and quality control in Huntington's disease - Pedro Guedes-Dias (2016)
Huntington's disease (HD) is an inherited neurodegenerative disorder caused by polyglutamine expansion mutations in the huntingtin protein. Despite its ubiquitous distribution, expression of mutant huntingtin (mHtt) is particularly detrimental to medium spiny neurons within the striatum. Mitochondrial dysfunction has been associated with HD pathogenesis. Here we review the current evidence for mHtt-induced abnormalities in mitochondrial dynamics and quality control, with a particular focus on brain and neuronal data pertaining to striatal vulnerability. We address mHtt effects on mitochondrial biogenesis, protein import, complex assembly, fission and fusion, mitochondrial transport, and on the degradation of damaged mitochondria via autophagy (mitophagy). For an integrated perspective on potentially converging pathogenic mechanisms, we also address impaired autophagosomal transport and abnormal mHtt proteostasis in HD.